Taxonomic revision of the microleafhopper genus Limassolla Dlabola from Korea (Hemiptrea: Cicadellidae: Typhlocybinae) - Hossain, Md. Shamim; Kwon, Jin Hyung; Suh, Sang Jae; Kwon, Yong Jung (Zootaxa, 2019)
Four species belonging to the genus Limassolla Dlabola, 1965 from Korea are revised. Among them, L. koreana sp. nov., an occasional pest of persimmon trees (Diospyros kaki) is new to science. L. macrobipunctata Choe, 1986 (nom. nud.) is validated by providing a description and illustration, and L. multipunctata (Matsumura, 1920) is newly recorded for the Korean fauna. Descriptions, illustrations and a key to the Korean species are provided here.